TEACHING GEOGRAPHY IN AZERBAIJAN. PROBLEMS WITH TEXTBOOKS AND TEACHERS. HISTORY OF DEVELOPMENT OF TEACHING METHODOLOGY. - Вердиева, Мирвари (Pedagogy and Psychology, 2023)
Summary It is the first time that the study of the history of teaching geography in secondary schools of Azerbaijan has become a subject of research. Author studies the establishment of schools in Azerbaijan, the involvement of children in the education process and the history of the place of geography as a new discipline in the school curricula. In addition, the author studies the teaching of geography by school grades and the number of hours per week compared to other school subjects. She studies the curricula of secondary schools in the former republics of the USSR, now independent states, and makes comparisons on the subject of geography. The present paper is also a study of the role of Azerbaijani intellectuals in writing textbooks based on the significance of personal development in acquiring geographical knowledge and skills. Author has provided the names of such intellectuals, as well as samples from their textbooks and teaching aids. Author has also explained the structure and content of the textbooks and their role in the independent acquisition of geographical knowledge and skills. Author analysed and studied the opening of new schools, the improvement of existing ones, the establishment and activities of educational societies to meet the growing demand for education in Azerbaijan since the 1900s. This includes the study of the practical measures taken at different times to provide schools with qualified teachers, the importance of organising training courses for teachers and establishing the Azerbaijan Men's Institute and its subsequent transformation into a state pedagogical institute. The research covers the issues related to the teaching of geography, as well as the emergence and development of methodology of teaching. The methodology of acquiring geographical knowledge and skills in Azerbaijan has been studied under two groups: public methodology and scientific methodology. The research provides information on the dependence of economic activities of the Azerbaijani population on the methodology of studying the environment, making observations and conservative use of events and natural components, as well as the mechanism of transmission of this knowledge to the next generations. The development of scientific methodology has been studied on the basis of archival materials.